Determinants and matrices - Aitken, A. C. (Edinburgh Oliver & Boyd, 1954)
Determinants and matrices, in linear algebra, are used to solve linear equations by applying Cramer$1 (Bs rule to a set of non-homogeneous equations which are in linear form. Determinants are calculated for square matrices only. If the determinant of a matrix is zero, it is called a singular determinant and if it is one, then it is known as unimodular.s
Keywords: Algebra; Determinants; Mathematics